(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to analyse the role played by the United Nations Security Council as regards nuclear disarmament and non-proliferation. It can be seen how the body responsible for maintaining peace within the universal organisation has gathered more power and authority in this area over time. Moreover, this paper discusses the attitude adopted by the Security Council to the different cases of nuclear proliferation. Its goal is twofold: to examine to what extent the positions of the different members of the Security Council are able to affect the Council’s actions, as well as to analyse their influence on the nuclear non-proliferation and disarmament regime.